Thermoelectric characteristics of Pt-silicide/silicon multi-layer structured p-type silicon. (15th March 2015) - Choi, Wonchul; Jun, Dongseok; Kim, Soojung; Shin, Mincheol; Jang, Moongyu
Abstract: Electric and thermoelectric properties of silicide/silicon multi-layer structured devices were investigated with the variation of silicide/silicon heterojunction numbers from 3 to 12 layers. For the fabrication of silicide/silicon multi-layered structure, platinum and silicon layers are repeatedly sputtered on the (100) silicon bulk substrate and rapid thermal annealing is carried out for the silicidation. The manufactured devices show ohmic current–voltage (I–V) characteristics. The Seebeck coefficient of bulk Si is evaluated as 195.8 ± 15.3 μV/K at 300 K, whereas the 12 layered silicide/silicon multi-layer structured device is evaluated as 201.8 ± 9.1 μV/K. As the temperature increases to 400 K, the Seebeck coefficient increases to 237.2 ± 4.7 μV/K and 277.0 ± 1.1 μV/K for bulk and 12 layered devices, respectively. The increase of Seebeck coefficient in multi-layered structure is mainly attributed to the electron filtering effect due to the Schottky barrier at Pt-silicide/silicon interface. At 400 K, the thermal conductivity is reduced by about half of magnitude compared to bulk in multi-layered device which shows the efficient suppression of phonon propagation by using Pt-silicide/silicon hetero-junctions. Highlights: Silicide/silicon multi-layer structured is proposed for thermoelectric devices. Electric and thermoelectric properties with the number of layer are investigated. An increase of Seebeck coefficient is mainly attributed the Schottky barrier. Phonon propagation is suppressed with the existence of Schottky barrier. Thermal conductivity is reduced due to the suppression of phonon propagation.